Construcción del sistema para el manejo de líquidos residuales en las trampas de aceite de la planta MAN, bajo el proceso de evacuación de aceite en Sopesa S.A (2020)
The main objective of the project was to eliminate liquid spills and improve the working conditions of the operators at the SOPESA S. A electrification plant on the Island of San Andrés, given that in the dependency of the MAN plant, proper management is not carried out to environmental waste, having a manual process of dumping and collecting liquids. The construction of the semi-automatic liquid handling system allowed to correctly handle the residues of the oil traps at the Manhole plant. A procedure is proposed to evaluate the performance of the System to reduce spills and environmental damage.